Prediction of fetal anemia by middle cerebral artery Doppler - S. El. Shourbagy; M. Elsakhawy (Middle East Fertility Society Journal, 2012)
Objectives: To assess the value of peak systolic velocity in the middle cerebral artery (MCA) in prediction of fetal anemia as a non invasive method in non hydropic fetuses. Methods: The study included 30 pregnant women with non hydropic fetuses and with known red cell antibodies. Full ultrasound examination was done and peak velocity of systolic cerebral blood flow in MCA was measured. If severe anemia was suspected, fetal blood sampling by cordocentesis was performed. Results: Thirty fetuses were examined, 22 were anemic and eight had a hemoglobin value within a normal range. The mean MCA peak systolic velocity for fetus with the normal hemoglobin (Hb) was 48.98 ± 13.94 while that for the anemic fetus was 64.79 ± 11.97 and P = 0.004. Sensitivity of increased peak velocity of systolic blood flow in MCA for prediction of fetal anemia was 90.5% and specificity was 78.6%. Conclusion: Doppler of peak velocity of systolic blood flow in MCA can be reliable in predicting anemia so delaying invasive methods until treatment (blood transfusion) is expected to be necessary.